Star Trek, Discovery. Season one [videorecording (DVD)] - Semel, David; Kane, Adam; Martin, Sonequa; Jones, Doug, 1960-; Latif, Shazad, 1988-; Roddenberry, Gene (Paramount, 2018)
Follow the adventures of the crew of the spaceship Discovery as they travel through the universe and encounter alien life forms.